COGNITIVE PROCESSES INVOLVED IN UNDERSTANDING HABITUAL STRUCTURES (Web of Teachers: Inderscience Research, 2025)
The comprehension of habitual structures in language involves a range of cognitive processes that allow individuals to recognize, interpret, and predict patterns of behavior and meaning. This article explores the cognitive mechanisms underlying the understanding of habitual constructions, including memory retrieval, pattern recognition, inferencing, and temporal processing. We also examine how these processes interact with linguistic input and contextual cues to shape interpretation, and consider the implications for second language acquisition and language disorders.